Acute kidney failure after total knee arthroplasty revision with antibiotic-impregnated cement spacer - Mazza, Daniele (Orthop Rev (Pavia), 2020)
Gentamicin-impregnated cement beads and spacers are frequently used in case of infective complications after Total Knee Arthroplasty (TKA). A great number of studies in the literature demonstrated that the local administration of gentamicin produces high local antibiotic levels but low serum and urine gentamicin concentrations. Gentamicin-impregnated cement spacer can induce nephrotoxicity in patients presenting major renal impairment susceptibility. We report a case of acute renal failure using a gentamicin-impregnated block spacer. An 83-year-old woman underwent a gentamicinimpregnated bone–cement spacer implant because of an infected TKA removal. Three days later patient clinical status got worse reporting a decreased urine output and increasing C-reactive protein (CRP), Serum Creatinine (SCr) and Blood Urea Nitrogen (BUN). Because the symptoms could be related to the knee spacer lead us to the decision of gentamicin-impregnated cement spacer removal. The day following the removal procedure showed progressive improvement of general condition with evidence of SCr and BUN normalization. Gentamicin-impregnated cement spacer can induce nephrotoxicity in patients presenting major renal impairment susceptibility.